A Systematic Review and Meta-Analysis on the Number of Adjuvant Temozolomide Cycles in Newly Diagnosed Glioblastoma - Attarian, Fahimeh; Taghizadeh-Hesary, Farzad; Fanipakdel, Azar; Javadinia, Seyed Alireza; Porouhan, Pejman; PeyroShabany, Babak; Fazilat-Panah, Danial (Frontiers in Oncology, 2021)
Background: In newly diagnosed glioblastoma, radiation with concurrent and adjuvant (six cycles) temozolomide (TMZ) is the established standard of postsurgical care. However, the efficacy of extending adjuvant TMZ therapy beyond six cycles has remained unknown. Methods: We searched PubMed, Web of Science, Scopus, and Embase up to October 1, 2021. The search keywords were “glioblastoma,” “adjuvant chemotherapy,” and their synonyms. The data of randomized clinical trials were extracted and included in this meta-analysis if they had reported patients’ median overall survival (OS) or median progression-free survival (PFS). The standard and extended chemotherapy regimens were considered as adjuvant TMZ up to six cycles and beyond six cycles (up to a total of 12 cycles), respectively. The median OS and median PFS were pooled and compared. Results: Four studies with 882 patients (461 patients for the standard chemotherapy group and 421 patients for the extended chemotherapy group) were included in this meta-analysis. The extended TMZ regimen was associated with a nonsignificant improvement in PFS [12.0 months (95% CI 9.0 to 15.0) vs. 10.0 months (95% CI 7.0 to 12.0), P = 0.27] without corresponding improvement in OS [23.0 months (95% CI 19.0 to 27.0) and 24.0 months (95% CI 20.0 to 28.0), P = 0.73]. Conclusions: In newly diagnosed glioblastoma, continuing adjuvant TMZ beyond six cycles was not shown to increase PFS and OS.